Practical questions of the Aragonese spousal Consortium - Medrano Sánchez, José Ignacio (Revista de derecho aragonés, 2024)
Distinguishing between “practical” and conceptual or academic issues has always seemed to me a futile and even contradictory endeavor. Those who apply the law must necessarily begin with the conceptual framework of the institution or institutions involved in a given conflict. Only in this way can the solution to these conflicts be approached with a minimum of guarantees and professional competence. Therefore, it seems essential to me, if one intends to address the practical problems arising in the context of spousal property relations, to first address the notion and characterization of the marital partnership, perhaps one of the most complex property phenomena in our legal system, and then proceed to record and address, through cases analyzed in jurisprudence, these practical issues.